ESRA19-0708 Optimal conduct of lumbar medial branch neurotomy. (30th August 2019) - Provenzano, D
Abstract : Introduction: Spine pain is associated with significant health and socioeconomic costs to the individual suffering from the condition and the healthcare system. 1 Spine pain is often difficult to isolate and diagnose. Zygapophysial (facet) joint mediated pain has been identified as a source of chronic low back. It has been estimated that approximately 30% of adults experience low back pain from lumbar facet joints. 2 In individuals with low back pain, the prevalence of the lumbar facet varies with age and ranges from 15% in younger patients to 45% in older patients. 3 4 Lumbar radiofrequency ablation (RFA) is a technique often employed to treat pain originating from the lumbar facet joints. 5 Substantial growth has occurred in the utilization of RFA to treat lumbar facet joint mediated pain. In the United States during the years of 2007 to 2016, there was a 131% overall increase (9.7% annually) in RFA sessions performed per 100, 000 enrollees per year. In addition to the number procedures increasing, costs have also increased. The lumbar RFA cost per 100, 000 enrollees increased 12.2% annually from 2007 to 2016. 6 Studies examing the clinical efficacy of lumbar RFA have shown mixed results. 5–10 Studies that have utilized stringent patient selection and a clinical practice guideline recommended technique for lumbar RFA have demonstrated improvements in pain control and function. 5 8 11 This lecture will discuss strategies to optimize clinical outcomes when performing lumbar RFA. Areas covered will include relevant anatomy, patient selection and optimal procedural steps to enhance lumbar RFA clinical outcomes and safety. Anatomy: The lumbar facet joints are synovial joints formed by the superior and inferior articular processes of each respective vertebral body. In the lumbar spine the superior articular facet is anterior and lateral to the inferior articular facet. Each joint has a fibrous joint capsule, a synovial membrane, and a hyaline cartilage. 12 Fat also exists within the intra-articular space. The adipose tissue pads and fibro-adipose meniscoids act as a protective barrier similar to a meniscus in a knee joint. At its thickest interval, the cartilage is approximately 2 mm. The facet joint is small, typically 1–2 mL in volume. Areas of the cartilage develop erosion and thinning with aging. 13 When an individual stands for prolonged periods of time, the lower facet joints (L3-L4, L4-L5, L5-S1) experience a greater proportion of the axial load. 14 The facets contribute 40% to torsional load resistance in the lumbar spine. The facet joints assist in resisting forward translation, rotation, compressive loads, and shearing forces generated in the lumbar spine. By resisting these movements, they assist in the protection of the intervertebral disc. 15 The innervation of the lumbar facet joints arises from the L1 to L4 medial branches of the dorsal rami and the L5 dorsal ramus. As a spinal nerve exits the neural foramen, it divides into ventral and dorsal primary rami. The L1 through L4 dorsal rami divide consistently into 2 branches, medial and lateral. At times, there is a third branch, the intermediate branch. The intermediate branch may also arise from the lateral branch. 16 The medial branch, which provides innervation to the facet joint, traverses the junction of the transverse and the superior articular processes. Each facet joint is innervated by either medial branches of the dorsal rami or dorsal ramus (L5) from the superior vertebral level and the same vertebral level. For example, the L4-L5 facet joint is innervated by the L3 and L4 medial branches. The medial branch is held in position and covered by the mamillo-accessory ligament. 16 17 The mamillo-accessory ligament is not a true ligament because it connects two points on the same bone: the accessory process located on the transverse process and the mamillary process located on the superior articular process. The medial branch is covered by the mamillo-accessory ligament distal to the middle of the neck of the superior articular process. The L5 dorsal ramus exists in the groove formed by the sacral ala and the superior articular process of S1. 18 Based on the surgical anatomy of the lumbar medial branch, traditional RFA ablation electrodes should be inserted obliquely from below with the active tip crossing the neck of the superior articular process so that the active tip is parallel to the target nerve. On the lateral fluoroscopic view, the active tip should lie opposite the middle two quarters of the superior articular process. When targeting the L5 dorsal ramus, the active tip should lie opposite the middle and posterior thirds of the S1 articular process on the lateral fluoroscopic view. Patient selection: One of the first steps in optimizing results with lumbar RFA is selecting patients who have been appropriately diagnosed with symptomatic facet joint arthritis. Radiological imaging and history and clinical examination are not adequate to diagnose facet joint mediated pain. 3 Evidence of facet joint arthritis on radiographic imaging does not correlate with low back pain. An ancillary project of the Framingham Heart Community-based Population study of 3529 participants discovered a high prevalence of facet joint osteoarthritis. In the 40 to 80 age bracket, 59.6% of males and 66.7% of females had CT radiographic imaging findings of facet joint osteoarthritis indicating that facet joint osteoarthritis increased with age. 19 The L4-L5 facet had the highest prevalence of arthritic changes. No association was found between the facet joint osteoarthritis identified by CT scan and low back pain. 19 Since the ability to diagnose facet joint mediated pain from radiographic imaging and physical examination is poor, diagnostic lumbar medial branch blocks performed under fluoroscopic guidance have been advocated as a screening method prior to progressing forward to RFA. 20 21 When performing diagnostic lumbar medial branch blocks, it is important to understand the implications of different block strategies including the volume of local anesthetic utilized, single verse comparative local anesthetic blocks, utilization of radiographic contrast to exclude vascular uptake, and optimal cutoff required for pain relief prior to proceeding to RFA ablation. Multiple strategies are employed to reduce the number of false negative and false positive blocks. Reasons for false positive blocks include the placebo effect and spread of the injectate to other pain generating structures. For example, the use of a lower target point (midway between the upper border of the transverse process and the mamillo-accessory ligament) and a low volume of injection (0.3 to 0.5 mL) are recommended to increase the specificity of the block. 22 23 When performing diagnostic lumbar medial branch blocks debate continues to occur over the optimal cutoff point that should be considered a positive response with regards to percent of pain relief. Some have advocated at least 80% pain relief as evidence for a positive response. 24 Cohen et al. 25 demonstrated that, when using the more stringent criteria of 3 80% pain relief threshold from diagnostic blocks instead of the 3 50% threshold, the success rates with RF denervation did not improve. In addition, more stringent criteria may lead to higher false negative rates with the diagnostic blocks and result in withholding RF denervation from individuals that may improve with treatment. Technical factors: Technical factors also play a critical role in optimizing the success rate for lumbar medial branch RFA. Medial branches are small and have a diameter less than 2 mm. 26 The L5 dorsal ramus has a transverse diameter less than 0.5 mm. 27 The small size of the target structure and the limited size of RFA ablation zone further necessitate the need for attention to methods of optimizing RFA lesioning. Thermal RFA involves the use of high-frequency alternating current (300, 000–500, 000 Hz) for high temperature tissue heating that results in irreversible cellular damage. 28 In order to increase the odds of lesioning the medial branch, multiple methods have been put in place to enhance lesion size. Common techniques that can be utilized to enhance lesion size include increasing the temperature, increasing the diameter of the electrode cannula, increasing the size of the active tip and increasing lesion time. Additional methods that can be utilized to increase lesion size include fluid pre-injection, modification of the electrode tip and the use of internally cooled electrodes. 29–33 Conclusion: Radiofrequency ablation is an effective strategy to treat pain in individuals suffering from low back pain associated with the facet joint. In order to effectively perform RFA, it is of critical importance that physicians understand the relevant anatomy of the medial branch and dorsal rami, optimal technical steps, and patient selection. References: Pain Physician . 2009;12(4):E225–264. Pain Med . 2015;16(8):1453–1454. Annals of the Rheumatic Diseases . 1995;54(2):100–106. Spine . 1994;19(10):1132–1137. Spine J . 2017. Spine J . 2019;19(6):1019–1028. Jama . 2017;318(1):68–81. Spine . 2008;33(12):1291–1297; discussion 1298. The bone & joint journal . 2016;98-b(11):1526–1533. Cochrane Database Syst Rev. 2015(10):Cd008572. Spine. 2000;25(10):1270–1277. Clinical Anatomy of the Lumbar Spine and Sacrum. Vol Fourth edition: Elsevier Churchill Livingston; 2005. Spine. 1986;11(7):739–745. Spine. 1983;8(3):327–330. Spine. 2008;33(25):2741–2748. Pain medicine (Malden, Mass). 2004;5(3):289–298. Spine. 1981;6(2):162–167. Spine. 1983;8(3):286–293. Spine. 2008;33(23):2560–2565. Anesthesiology. 2018. International Spine Intervention Society Practice Guideline for Spinal Diagnostic and Treatment Procedures. 2nd edition ed. San Francisco: International Spine Intervention Society; 2013. Best practice & researchClinical anaesthesiology. 2002;16(4):565–578. Spine. 1997;22(8):895–902. The spine journal: official journal of the North American Spine Society. 2008;8(1):56–64. The spine journal: official journal of the North American Spine Society. 2008;8(3):498–504. British journal of rheumatology. 1987;26(2):93–98. Reg Anesth Pain Med. 2014;39(6):456–464. Critical Reviews in Biomedical Engineering. 2010;38(1):53–63. Regional anesthesia and pain medicine. 2010;35(4):338–342. Regional anesthesia and pain medicine. 2013;38(2):112–123. Reg Anesth Pain Med. 2015;40(2):112–124. Reg Anesth Pain Med. 2018;43(7):776–788. Pain Physician. 2014;17(2):E175–211.